2015
DOI: 10.4269/ajtmh.15-0245
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Compliance with Long-Term Antimalarial Chemoprophylaxis in American Soldiers in Afghanistan

Abstract: Abstract. Long-term antimalarial chemoprophylaxis is currently used by deployed U.S. military personnel. Previous small, short-term efficacy studies have shown variable rates of side effects among patients taking various forms of chemoprophylaxis, though reliable safety and tolerability data on long-term use are limited. We conducted a survey of troops returning to Fort Drum, NY following a 12-month deployment to Operation Enduring Freedom, Afghanistan from 2006 to 2007. Of the 2,351 respondents, 95% reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 26 publications
0
35
0
2
Order By: Relevance
“…38,39 However, other studies have found that compliance with mefloquine is higher than with doxycycline (American Soldiers: 80% versus 60%; Turkish troops: 61% versus 56%; Australian travelers: 78% versus 68%). [40][41][42] However, how compliance is defined is important in interpreting these findings. In the cited studies, estimated compliance rates correspond to taking the medication as prescribed without missing a dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 However, other studies have found that compliance with mefloquine is higher than with doxycycline (American Soldiers: 80% versus 60%; Turkish troops: 61% versus 56%; Australian travelers: 78% versus 68%). [40][41][42] However, how compliance is defined is important in interpreting these findings. In the cited studies, estimated compliance rates correspond to taking the medication as prescribed without missing a dose.…”
Section: Discussionmentioning
confidence: 99%
“…This is different than completely stopping the medication, which was only reported between 3% and 5% for either medication among service members. 41,42 Complete cessation of the medication would impact this study more profoundly than missing doses, but this is also expected to occur among a small percentage of subjects. If subjects stopped taking prescribed prophylaxis due to adverse events and if the adverse events resulted in a medical encounter, then it would have been captured and the risk period would have been censored appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical synapses might even be targeted in combination with the external cueing of memory traces during sleep to erase maladaptive behavior and/or strengthen beneficial 22 alternatives (Hauner et al, 2013). Moreover, our result of sleep-associated mnemonic impairments following mefloquine intake may also shed new light on reports that mefloquine regimens for malaria prevention can trigger adverse neuropsychiatric effects (Chen et al, 2007;Saunders et al, 2015). To test declarative memory formation, forty word-pairs were first presented to and then immediately recalled by the participants in response to the first word.…”
Section: Discussionmentioning
confidence: 66%
“…Our study provides important data on the compliance, tolerability, and acceptability of the 3-day schedule of atovaquone/proguanil in healthy travellers, and the potential for using this schedule for malaria prophylaxis. The high compliance of (97.7%) is impressive compared to previous studies, which have reported 24-89% for the standard schedule of atovaquone/proguanil [29,32], 65-80% for proguanil [6,33], 60-79% for doxycycline [6,34], and 68-80% for mefloquine [6,33,34]. Considering that poor compliance to chemoprophylaxis is a major contributing factor to travel-related malaria, the 3-day schedule has the potential to significantly reduce malaria in travellers.…”
Section: Discussionmentioning
confidence: 83%